Plant-base remedies for the management of mental health disorder in Buea Municipality, Southwest Cameroon - Arrey, Doris Besem; Tajeukem, Vice Clotexe; Essomo, Etanke Sylvie; Ayamba, Ayuk Brandon; Fonge, Beatrice Ambo (Journal of Medicinal Herbs and Ethnomedicine, 2025)
Mental health issue (mental illness) is the malfunctioning of individuals as a result of altering their behaviour, reasoning, life achieving goals and as well as emotions of the affected individual. In Buea, there is a rise in mental health issues as a result of socioeconomic crises and an increase in modernization that has resulted in increased school dropout. The health facilities in the municipality are very limited in managing these increased mental health issues. As a result, plants have come in as alternatives. The study was conducted to evaluate the different plants used in managing mental health disorders. Field surveys, interviews and semi-structured questionnaires were used to collect data from this study. RFC = FC/N (0<RFC<1), Use Reports (UR), the use value (UV) and the informant agreement ratio (IAR) were computed. Twenty-two plants were used to treat one or more categories of mental illness in Buea municipality. The mental illness categories were depression (52.5%), stress (26.3%), fear (21.3%), anger (13.8%) and anxiety (10%). Ocimum gratissimum, Aframomum melegueta and Afrostyrax lepidophyllus were reported to treat four of the five categories of mental illness. The medicinal plants with the highest Frequency of citation were A. melegueta, Ageratum conyzoides, Voacanga africana, O. gratissimum and A. lepidophyllus (42, 32, 26, 22, 21) respectively. For the used reports, 168, 96, 88, 84 and 78 were reported for A. melegueta, A. conyzoides, O. gratissimum, A. lepidophyllus and V. africana respectively. Leaves were the most used plants parts and the mode of preparation was by decoction. In conclusion, these plants will be further screened to improve on drug discovery in mental health management.